Dari Eksplorasi Minyak Hingga Membangun Kota: Dumai Kota Perusahaan Caltex 1956-1970-an - Simbolon, Frido Paulus (Medan Resource Center, 2024)
This research examines the development of Dumai as a company town, where its growth is closely tied to the role of a multinational oil company, Caltex. The study addresses the question of how Caltex developed and shaped Dumai, beginning with the company's arrival in 1956. Caltex initially operated in Minas, Duri, and Rumbai but needed a strategic port to export crude oil from its fields, leading to the selection of Dumai. Using historical methods and literature review, this research chronicles Caltex’s establishment of Dumai as a key operational and distribution center. The findings reveal that since Caltex's arrival, Dumai has rapidly transformed into a company town, a development largely driven by its oil industry operations. The study concludes that Dumai’s urban growth is a direct result of Caltex's significant role in the city’s management and infrastructure.